Managerial Analysis, Dividend Policy, Oportunistic Behavior, and Profitability on the Value of Manufacturing Sector Companies Listed on the Indonesia Stock Exchange - Moh. Abd. Rahman; Eva Agustiany P (Fakultas Ekonomi dan Bisnis Islam, 2023)
Abstract_This research aims to test the influence of managerial ownership, dividend policy, opportunistic behavior and profitability to firm value. The object in this research is manufacture companies listed on the Indonesia stock exchange in the period 2011-2015. On this research obtained a sample of 53 with a period of observation for 5 years. Data analysis techniques used to use multiple linear analysis. Based on the results of the research conducted, the results obtained that the managerial ownership has a negative effect not significantly on the firm value, dividend policy has a significantly positive effect on the firm value, opportunistic behavior has a significantly negative effect on the firm value while the profitability has a significantly positive effect on the firm value, so that it can be concluded that only the opportunistic behavior and profitability have influence on the firm value.